Identifying the earliest citrus responses to Candidatus Liberibacter asiaticus infection: a temporal metabolomics study - Li, Jingwen; Wang, Yuanzhi Zimmy; Gmitter, Fred G.; Wang, Yu (Frontiers in Plant Science, 2024)
The global citrus industry faces a great threat from Huanglongbing (HLB), a destructive disease caused by ‘Candidatus Liberibacter asiaticus’ (CLas) that induces significant economic losses without any known cure. Understanding how citrus plants defend against HLB, particularly at the early stages of infection, is crucial for developing long-term solutions. This study investigated the earliest metabolic responses of fresh citrus leaves to CLas infection using untargeted metabolomics and machine learning models. HLB-tolerant and HLB-sensitive cultivars were compared to analyze their biochemical reactions within 48 hours post-infection. HESI/Q-Orbitrap MS analysis identified temporal differential metabolites, revealing distinct metabolic pathways activated in response to CLas infection. Both cultivars responded by increasing specific metabolite concentrations, such as flavonoids, within 2 hours post-infection, but the HLB-tolerant cultivar maintained higher levels throughout the 48-hour period. This early metabolic activity could influence long-term plant health by enhancing disease resistance and reducing pathogen impact. These findings provide potential biomarkers for breeding HLB-resistant cultivars and offer valuable insights for developing sustainable management strategies to mitigate the impact of HLB on the citrus industry, ensuring its long-term productivity and economic viability.